ProBDNF Induces Neuronal Apoptosis via Activation of a Receptor Complex of p75(NTR) and Sortilin - Teng, Henry K. (J Neurosci, 2005)
Brain-derived neurotrophic factor (BDNF) is best characterized for critical roles in neuronal survival, differentiation, and synaptic modulation mediated by the TrkB receptor tyrosine kinase. Developmentally regulated death signaling by BDNF has also been demonstrated via activation of p75(NTR). Because recent studies suggest that proNGF, the precursor form of NGF, is more active than mature NGF in inducing apoptosis after binding to p75(NTR) and a coreceptor, sortilin, we asked whether the precursor of BDNF (proBDNF) is also a proapoptotic ligand in the nervous system. proBDNF is secreted by cultured neurons, and recombinant proBDNF binds to sortilin. In sympathetic neurons coexpressing sortilin and p75(NTR), we found that proBDNF is an apoptotic ligand that induces death at subnanomolar concentrations. In contrast, mature BDNF, but not proBDNF, is effective in inducing TrkB phosphorylation. proBDNF effects are dependent on cellular coexpression of both p75(NTR) and sortilin, because neurons deficient in p75(NTR) are resistant to proBDNF-induced apoptosis, and competitive antagonists of sortilin block sympathetic neuron death. Moreover, addition of preformed complexes of soluble sortilin and proBDNF failed to induce apoptosis of cells coexpressing both sortilin and p75(NTR), suggesting that interaction of proBDNF with both receptors on the cell surface is required to initiate cell death. Together with our past findings, these data suggest that the neurotrophin family is capable of modulating diverse biological processes via differential processing of the proneurotrophins.